2012
DOI: 10.3109/s10165-011-0550-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphea associated with the use of adalimumab: a case report and review of the literature

Abstract: Therapy with TNF blockers may induce cutaneous adverse events, but the development of morphea, a localized scleroderma lesion, is extremely infrequent. We describe a 37-year-old man with ankylosing spondylitis treated with adalimumab who developed morphea lesions in the lower limbs after 12 months of treatment. Adalimumab was discontinued, which resulted in progressive improvement in the skin lesions, with only mild hyperpigmentation remaining. We also review reports of morphea and other adverse cutaneous even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…These autoimmune CAE conditions may occur at any time during treatment with TNF antagonists, although they frequently occur within the first year. Withdrawal of therapy with a biologic agent was frequently followed by complete recovery (). Therefore, the prognosis and outcome of these events differ from non–drug‐induced immune‐mediated conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These autoimmune CAE conditions may occur at any time during treatment with TNF antagonists, although they frequently occur within the first year. Withdrawal of therapy with a biologic agent was frequently followed by complete recovery (). Therefore, the prognosis and outcome of these events differ from non–drug‐induced immune‐mediated conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the prognosis and outcome of these events differ from non–drug‐induced immune‐mediated conditions. In cases of alopecia areata, inhibition of TNF could promote the dysregulation of interferon‐α and activation of self‐reactive T cells leading to skin lesions (). In morphea, it has been suggested that TNF antagonists may induce the profibrotic cytokine transforming growth factor β1, involved in skin thickening, although T cell activation has been reported as well ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse events include infections (eg, herpesvirus), immune‐mediated conditions (eg, psoriasis, alopecia areata, cutaneous lupus erythematosus, cutaneous vasculitis, vitiligo, localized morphea and relapsing polychodritis), and neoplasms (eg, melanoma, non‐melanoma skin cancer, and benign neoplasms including a single report of fibroma) . In instances of morphea associated with adalimumab, it has been suggested that the drug might induce the profibrotic cytokine transforming growth factor β1, involved in skin thickening, although T‐cell activation is also possible The association of adalimumab with our patient's eruption may be purely coincidental, but it is possible this drug served as a “trigger,” precipitating the collagenoma formation. This hypothesis seems unlikely because the condition rapidly worsened after adalimumab was discontinued (Figure 6B).…”
Section: Discussionmentioning
confidence: 99%
“…44 Localized scleroderma secondary to adalimumab has been described in two patients, one of whom had Crohn's disease 45 and the other ankylosing spondilitis. 46 Biopsy showed dermal thickening with broad sclerotic collagen bundles, superficial perivascular infiltrate of lymphocytes and atrophy of adnexal structures. Finally, more recently, dusky plaques on the abdomen, thighs, flank and back developed in a patient on etanercept for psoriasis.…”
Section: Sclerosing Patternmentioning
confidence: 99%